TOPOGRAPHOANATOMICAL INTERRELATION OF THE PAROTID GLANDS WITH SURROUNDING ORGANS AND STRUCTURES IN 10-MONTH FETUSES OF HUMAN - Lavriv, L.P. (World of Medicine and Biology, 2012)
In 5 human fetuses 310,0-345,0 mm of the parieto-coccygeal length (10 months of fetal development) by means of the methods of habitual and thin anatomization controlled by the binocular loupe, makromikroskopy and morphometry been studied the anatomical specific characteristics of the organs and structures of the parotid region. Revealed seals fascial-fatty formations in the places from of the close topographoanatomical correlation of the relationships of the its organs and structures.